Social capital, investments, and external financing - Javakhadze, David; Ferris, Stephen P.; French, Dan W. (Journal of Corporate Finance, 2016)
This study examines the effects of managerial social capital on investment sensitivity to cash flow and Q. Using a large cross-country sample of companies for the period 1999–2012 and a traditional investment-Q framework, we discover that social capital reduces a firm's dependence on internally generated cash. We find that social capital is positively associated with investment sensitivity to Q. We further determine that social capital positively affects the sensitivity of external finance to Q, while inversely influencing the sensitivity of external finance to cash flow. These effects of social capital are stronger in markets characterized by the weak legal protection of investors. Our findings are robust to alternative model specifications, different variable measurements, and tests for endogeneity.